ChemInform Abstract: PBr3‐Mediated Unexpected Reductive Deoxygenation of α‐Aryl‐pyridinemethanols: Synthesis of Arylmethylpyridines. Issue 29 (June 2016) - Nishigaya, Yosuke; Umei, Kentaro; Watanabe, Daisuke; Kohno, Yasushi; Seto, Shigeki
Abstract: In an attempt to substitute the hydroxy group in the title compounds by a bromine, a direct reductive deoxygenation takes place to produce the desired final target compounds.